Application of Accounting Information System for Sales and Cash Receipts in an Effort to Improve Internal Control: Penerapan Sistem Informasi Akuntansi Penjualan dan Penerimaan Kas dalam Upaya Peningkatan Pengendalian Internal - Rahmadani, Hanun; Abidin, Fityan Izza Noor (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the Application of Accounting Information Systems Sales and Cash Receipts in Efforts to Improve Internal Control at PT. Prime Success Prosperous. This research is a type of descriptive research with a qualitative approach. The data needed in this study include primary data and secondary data. The primary data of this study were obtained from direct interviews with parties involved in sales and cash receipts at PT. Prime Success Prosperous. While the secondary data of this research was obtained from the literature study conducted by the researcher. The results of this study indicate that the Accounting Information System of sales and cash receipts applied by PT. Perdana Sukses Makmur has been going well even though it is still manual in receiving cash. This is supported by the existence of procedures that have to do with sales and cash receipts. As well as the existence of various functions with their respective duties and responsibilities along with the completeness of documents and records in sales and cash receipts.